BK Virus Associated Nephropathy, a Cause of Early Renal Allograft Dysfunction: A Single Centre Study - Shrestha, S.; Kerr, P.G.; Kanellis, J.; Polkinghorne, K.R.; Brown, F.; Yii, M.; Mulley, W. (Kathmandu University Medical Journal, 2017)
Background BK virus associated nephropathy (BKVN) is an important cause of early graft dysfunction in renal transplant recipients. The present study was carried out to determine the burden of BKVN in a single renal transplant centre in Australia.Method A retrospective analysis of de novo renal transplant recipients from 2010 to 2013 was performed to identify biopsy proven BKVN. Estimated glomerular filtration rate (eGFR) was compared at baseline, at BKVN diagnosis and 3 and 12 months post-diagnosis.Result Of the 317 de novo renal transplants recipients in the study period, 20 (6.3%) developed BKVN. The mean age was 54.8 ± 13.1 years and 13 (65%) were male. The mean time from transplant to BKVN was 8.7 ± 6.7 months with 17 (85%) diagnosed within 12 months. Four recipients each were diagnosed BKVN on 3 and 12 month surveillance biopsy. Six (30%) had normal eGFR at diagnosis. Mean eGFR at diagnosis was 38.8 ± 19.2 ml/min/1.73 m2, which was significantly lower (p < 0.01) than that at baseline (50.3 ± 16.4 ml/min/1.73 m2). eGFR improved numerically at 3 and 12 months post-diagnosis, however the difference was not significant. One patient had graft failure, 19 months after diagnosis.Conclusion BKVN generally occurs in first post-transplant year and is an important cause of early graft dysfunction. Surveillance biopsy helps in detecting subclinical BKVN.